A General Map of Transcriptional Expression of Virulence, Metabolism, and Biofilm Formation Adaptive Changes of Staphylococcus aureus When Exposed to Different Antimicrobials - Ren, Zun; Yu, Jinlong; Du, Jiafei; Zhang, Yubo; Hamushan, Musha; Jiang, Feng; Zhang, Feiyang; Wang, Boyong; Tang, Jin; Shen, Hao; Han, Pei (Frontiers in Microbiology, 2022)
Biofilm formation of Staphylococcus aureus is the major cause of implant-associated infections (IAIs). Antimicrobial treatment is one of the most effective therapeutic options for S. aureus infections. However, it can also lead to adaptive transcriptomic changes due to extreme selective pressure, which may increase the risk of antimicrobial resistance. To study the transcriptional changes in S. aureus upon exposure to antimicrobial agents, we obtained expression profiles of S. aureus treated with six antimicrobials (flucloxacillin, vancomycin, ciprofloxacin, clindamycin, erythromycin, and linezolid, n = 6 for each group). We also included an untreated control group (n = 8) downloaded from the Gene Expression Omnibus (GEO) database (GSE70043, GSE56100) for integrated bioinformatic analyses. We identified 82 (44 up, 38 down) and 53 (17 up, 36 down) differentially expressed genes (DEGs) in logarithmic and stationary phases, respectively. When exposed to different antimicrobial agents, we found that manganese import system genes and immune response gene sbi (encoding IgG-binding protein Sbi) were upregulated in S. aureus at all stages. During the logarithmic phase, we observed adaptive transcriptomic changes in S. aureus mainly in the stability of protein synthesis, adhesion, and biofilm formation. In the stationary phase, we observed a downregulation in genes related to amino biosynthesis, ATP synthesis, and DNA replication. We verified these results by qPCR. Importantly, these data could aid our understanding of the molecular mechanism underlying the proliferation and the antimicrobial resistance of S. aureus, leading to the identification of novel anti-infective targets to treat S. aureus infection.